Arms against fury Magnum photographers in Afghanistan - Dannin, Robert 1952- (PoweHouse Books, 2002)
Arms Against Fury examines the dramatic struggle of the Afghan people through the lens of Magnum photographers, dating back to co-founder George Rodger's documentation of the country's role in World War II. Ever since, Magnum's intrepid photographers have crisscrossed the country's striking landscape from the Central Asian steppes to the parched southern desert by way of the Hindu Kush mountains surrounding Kabul and the adjacent Panjshir Valley.